Fractionation curves of normal and pathological human serum with sodium thiosulfate (Revista Española de Fisiología, 1951)
The fractioning curves of serum with sodium thiosulphate, a salt suggested the first time in an earlier papen, are studied. From the average curves of a series of 12 and another of 35 sera the existencie of thre tnain points of inflection is established at the concentrations of 30,7, 35,5 and 44,1 g% of Na3S3H3. Theis actual existence is confirmed by statistical studies and by its persistence in pathological sera. Calculating on the basis of these points, the absolute and percentage valúes of the fractions delimitated by the results are found equivalents to the electrophoretic ones.The fractioning in 82 pathological sera has been obtained and by means of them it has been confirmed the existence of different types of plasmocitoma, the increase in y globulin in cirrosis of the liver and in two nephrotic sera the increase in precipitation in the 9’ and a zone. Up to now no pathological curve, that- does not descend to withiu the globulin zone, has been observed.Finally, hit may be considered that the fractioning with sodium thiosulphate offers theoretical and practical advantages over all salts so far suggested. Theoretically on account of the satisfactory coincidence of the fractions deduced from the inílección points found in its curve, with the electrophoretic ones. Practically because of its great solubility it es possible to prepare its Solutions easily and work at room temperature;íurthennore it precipitates rapidily and does not disturb the protein de- tcrmination in the fíltrate by Kjeldahl cr biuret reaction.